KEDUDUKAN MAJELIS PENGAWAS DAERAH DALAM MEWUJUDKAN NOTARIS YANG PROFESIONAL DI KOTA MATARAM - , Hannibal Antabogar ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine whether the Regional Supervisory Council (MPD) has been carrying out duties and responsibilities to a professional attitude Realising a Notary in Mataram, and any obstacles that arise and how the Regional Supervisory Council (MPD) to address these constraints. This study examines the nature of juridical impiris with primary data and secondary data. This study conducted two kinds of research that the research literature on primary legal materials and secondary studies by the document. Fieldwork was conducted by way of interview based interview guides. Based on the research conducted, the obtained results that the Supervisory Council of the Region shall appropriate authority by the existing rules. Mataram City Regional Supervisory Council also outreach to parties related to the profession of notary public among other elements, an element of Academic Affairs and the Indonesian National Police. The constraints faced by the Supervisory Council area in general there is always a way to handle it, unless the initiative of the Chairman of the Supervisory Council area alone. This is due to the lack of government attention to the Supervisory Council area Mataram, shall perform their duties in accordance with law even without any remuneration or Hororarium and only use the facilities and inadequate infrastructure.